2015
DOI: 10.1016/j.reprotox.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity in rats of a hemoglobin-based oxygen carrier results from impeded function of the inverted visceral yolk sac

Abstract: HBOC-201 is a bovine-derived, cross-linked, and stabilized hemoglobin (250kDa) in physiological saline. Daily intravenous infusions of HBOC (1.95, 3.90, or 5.85g/kg/day) during gestational days (GDs) 6-18 in Sprague-Dawley rats caused fetal mortality, reduced birth weight, and malformations. Subsequent single-day infusions (5.85g/kg/day) showed that developmental toxicity was limited to GDs 7-9 when histiotrophic nutrition via the inverted visceral yolk sac (invVYS) is essential. Histiotrophic nutrition is rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It is known that human yolk sac does not function as a placenta in the sense of being able to transfer nutrients between the maternal and embryonic circulations (Boyd, 2012;DeSesso et al, 2012). In addition, it is reported that the HBOC-201 (hemoglobinbased oxygen carriers)-induced embryo toxicity is indeed due to the damage of the yolk sac, and is not expected to impact human development (Stump et al, 2015). Therefore, the embryo toxicity induced by dysfunction of the yolk sac in rats cannot likely be extrapolated to humans.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that human yolk sac does not function as a placenta in the sense of being able to transfer nutrients between the maternal and embryonic circulations (Boyd, 2012;DeSesso et al, 2012). In addition, it is reported that the HBOC-201 (hemoglobinbased oxygen carriers)-induced embryo toxicity is indeed due to the damage of the yolk sac, and is not expected to impact human development (Stump et al, 2015). Therefore, the embryo toxicity induced by dysfunction of the yolk sac in rats cannot likely be extrapolated to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers currently think that the optimal particle size for HBOCs is 128 kD or higher [33], but there is no consensus as to the appropriate range of their molecular weights. For example, the average molecular weight of HBOC-201 (Biopure Co. Ltd, Cambridge, MA) is 250 kD and that of Zero-link (oxyVita Inc.) is higher than 20 MD [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…9). It is thought that the human yolk sac does not function as a placenta in the sense of being able to transfer nutrients between maternal and embryonal circulations 86 , 88 , 89 . Therefore, embryo toxicity induced by yolk sac dysfunction during the period before chorioallantoic placenta formation in rats cannot necessarily be extrapolated to humans.…”
Section: Comparison With Human Placentamentioning
confidence: 99%
“…Thus, an animal model that does not rely upon an inverted yolk sac for embryonic nutrition should be used to elucidate any potential risk of developmental toxicity caused by chemicals in humans. 89…”
Section: Comparison With Human Placentamentioning
confidence: 99%